2007
DOI: 10.1007/s10865-006-9092-1
|View full text |Cite
|
Sign up to set email alerts
|

Personal Digital Assistants are Comparable to Traditional Diaries for Dietary Self-Monitoring During a Weight Loss Program

Abstract: Dietary self-monitoring is considered the core of behavioral weight control programs. As software for personal digital assistants (PDA) has become more available, this study investigated whether the use of a PDA would improve dietary self-monitoring frequency and subsequent weight loss over the use of traditional paper diaries. One-hundred-seventy-six adults (BMI 25-39.9) participated in a 6-month behavioral weight control program. Treatment subjects (n = 61) were provided with a PalmZire 21 with Calorie King'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 37 publications
8
75
2
Order By: Relevance
“…With that being said, our rate of 58% of participants entering 3 meals per day is comparable to the rates found by Glanz et al [35] and likely greater that the rates reported by Yon et al [36] * We have incomplete data in waves 2 and 4. Older-generation PDAs did not back-up BalanceLog® data when battery power was lost, and thus we were subsequently unable to retrieve these data.…”
Section: Feasibility and Acceptability Of Pda-based Dietary Monitosupporting
confidence: 75%
See 1 more Smart Citation
“…With that being said, our rate of 58% of participants entering 3 meals per day is comparable to the rates found by Glanz et al [35] and likely greater that the rates reported by Yon et al [36] * We have incomplete data in waves 2 and 4. Older-generation PDAs did not back-up BalanceLog® data when battery power was lost, and thus we were subsequently unable to retrieve these data.…”
Section: Feasibility and Acceptability Of Pda-based Dietary Monitosupporting
confidence: 75%
“…In a behavioral weight loss program that included PDA-based self-monitoring, Yon et al found that participants submitted weekly e-journals 52% of the time. [35] However, adherence was defined as the availability of a weekly record regardless of the completeness of that record. Unless all meals were entered every day, the frequency of self-monitoring in the study by Yon et al is likely to be somewhat less than 52%.…”
Section: Feasibility and Acceptability Of Pda-based Dietary Monitomentioning
confidence: 99%
“…20 Few studies have examined the utility of portable electronic recording devices for promoting behavior change and weight loss, and findings have been mixed. For example, Yon and associates 21 found no group differences in weight loss or frequency of self-monitoring among participants assigned to self-monitor their dietary intake through either traditional methods or PDAs. However, in another 6-month intervention study, the use of PDAs increased adherence to dietary self-monitoring significantly more than traditional paper diaries.…”
Section: Introductionmentioning
confidence: 99%
“…These devices contained an integrated pre-defined drop-down list of foods, typically ranging from 180 to >4000 items (18) , and have been demonstrated to be comparable with traditional methods of dietary assessment (46)(47)(48) . Progressions in technology have however resulted in smartphone use surpassing PDA as the foremost mobile method of dietary assessment (16,26,49) , with growing research emerging into the use of smartphones to measure dietary intakes using both applications (app) and image-based methods (50) .…”
Section: Mobile Methods Of Dietary Assessmentmentioning
confidence: 99%